Examining Hope as a Transdiagnostic Mechanism of Change Across Anxiety Disorders and CBT Treatment Protocols. Issue 1 (January 2020) - Gallagher, Matthew W.; Long, Laura J.; Richardson, Angela; D'Souza, Johann; Boswell, James F.; Farchione, Todd J.; Barlow, David H.
Abstract: Hope is a trait that represents the capacity to identify strategies or pathways to achieve goals and the motivation or agency to effectively pursue those pathways. Hope has been demonstrated to be a robust source of resilience to anxiety and stress and there is limited evidence that, as has been suggested for decades, hope may function as a core process or transdiagnostic mechanism of change in psychotherapy. The current study examined the role of hope in predicting recovery in a clinical trial in which 223 individuals with 1 of 4 anxiety disorders were randomized to transdiagnostic cognitive behavior therapy (CBT), disorder-specific CBT, or a waitlist controlled condition. Effect size results indicated moderate to large intraindividual increases in hope, that changes in hope were consistent across the five CBT treatment protocols, that changes in hope were significantly greater in CBT relative to waitlist, and that changes in hope began early in treatment. Results of growth curve analyses indicated that CBT was a robust predictor of trajectories of change in hope compared to waitlist, and that changes in hope predicted changes in both self-reported and clinician-rated anxiety. Finally, a statistically significant indirect effect was found indicating that the effects of treatment on changes in anxiety were mediated by treatment effects on hope. Together, these results suggest that hope may be a promising transdiagnostic mechanism of change that is relevant across anxiety disorders and treatment protocols. Highlights: Hope is cognitive trait that predicts resilience and recovery from anxiety disorders This study examined hope as a transdiagnostic mechanism of change in CBT Transdiagnostic and four disorder specific CBTs all produced large increases in hope Intraindividual changes in hope were robust predictors of symptom trajectories Hope is a promising transdiagnostic mechanism of change across disorders and protocols